A study of stereotypic behaviours in Alzheimer's disease and frontal and temporal variant frontotemporal dementia. Issue 10 (20th October 2003) - Nyatsanza, S; Shetty, T; Gregory, C; Lough, S; Dawson, K; Hodges, J R
Abstract : Objective: To document the prevalence and pattern of stereotypic behaviour in patients with Alzheimer's dementia and frontal and temporal variants of frontotemporal dementia. Secondly, to examine the relationship between stereotypic and other neuropsychiatric behaviours. Methods: Patients with the following were studied; Alzheimer's disease (n=28), frontal variant frontotemporal dementia (fvFTD, n=18), and semantic dementia—the temporal lobe variant of FTD (n=13). All patients were assessed using the Neuropsychiatric Inventory (NPI), the Mini-Mental State Examination, Addenbrooke's Cognitive Examination, and the Clinical Dementia Rating scale. Patients were also rated on the newly devised Stereotypic and Ritualistic Behaviour (SRB) subscale, which was designed as an addendum to the NPI. Results: There was no significant difference across diagnostic groups in terms of age, sex, or severity of cognitive deficits. The overall NPI was significantly higher in patients with fvFTD compared with the other two groups, but fvFTD and semantic dementia showed a similar, and significantly increased, prevalence of stereotypic behaviours on the SRB subscale. Within the FTD group as a whole these behaviours were more likely to be complex, whereas in Alzheimer's disease, when present, such behaviours tended to be more simple stereotypies or stimulus bound repetitive behaviours. Stereotypic behaviours were not correlated with either disease severity or the extent of cognitive impairment in the fvFTD group, but were in the other two diagnostic groups. Conclusion: Complex stereotypic behaviours are a core feature of the dementing syndrome in FTD and may reflect early and specific deficits in orbitofrontal circuitry and basal ganglia involvement.